Physical and chemical characterization of residual palm (Elaeis guineensis Jacq.) biomass in the Peruvian Amazon - Neyra-Vasquez, Jessica Yanina (2022)
Introduction. The oil palm (Elaeis guineensis Jacq.) in the Peruvian Amazon has an installed production area of 72,861 ha, whose fruit processing generates solid residues such as the stalk and dry mesocarp. Objective. To determine the physicochemical characteristics of the residual biomass, stalk, and fruit fiber from palm oil extraction in the Peruvian Amazon, for its potential use in the elaboration of biodegradable materials. Materials and methods. During August to October 2020, 19.39 t/day of stalk and 13.05 t/day of oil palm fruit fiber were collected in Pucallpa, Neshuya District, Peru. Solubility analyzes in hot water and moisture were determined using the American standard test (American Society for Testing and Materials). The solubility in soda was obtained using the Technical Association of the Pulp and Paper Industry standard method. High performance liquid chromatography (HPLC) and refractive index (RI) detector were used to determine cellulose, hemicellulose, and lignin. Results. The physical properties of moisture (%) and solubility in soda (%) showed no differences between stalk and fiber. Both stalk and the fiber showed solubility in hot water, with values lower than 17 %. The chemical properties of the fiber were higher than those in the stalk, based on the percentage of cellulose, hemicellulose, and lignin. Conclusions. The physical and chemical results of oil palm stalk and fruit fiber would allow the development of appropriate technological processes for their conversion to biological products.